Public spending on agricultural productivity and rural commercialisation: A comparison of impacts using an economy‐wide approach - Aragie, Emerta A.; Balié, Jean (John Wiley & Sons, 2021)
Many developing countries have identified a set of strategic objectives and a longlist of investment areas to promote agricultural production and ensure food security. However, most of these countries lack the financial and technical capacity to execute all of the strategic objectives and investment areas, calling for a robust comparison of their effects.Taking the case of Ethiopia as an example, this study employs an economy‐wide model and assesses the relative efficiency of alternative investment options on agricultural performance and household welfare. These agricultural investment policies are evaluated under three alternative funding modalities: budget reallocation, donor financing and tax revenue.To account for the linkage, and direct and indirect impacts of alternative public expenditure policies, this study adapts an economy‐wide general equilibrium model for Ethiopia calibrated to a well disaggregated social accounting matrix representing the economic structure in 2010.Results show that the public expenditure options examined could cause significantly different production and welfare responses. Productivity‐enhancing interventions such as input subsidy and irrigation development have superior output and welfare consequences, while policies aimed at smallholder commercialization such as infrastructural development aimed at cutting marketing margins have the least effect, suggesting a need to first prioritize relaxing supply constraints. This ranking of the agricultural policies is robust to the investment financing modalities considered. We, however, observe that financing these projects through income tax could be detrimental to the welfare of urban households.Results show that in a supply‐constrained economy like that of Ethiopia, governments should focus on agricultural production and productivity‐enhancing interventions (at least in the short run). Reallocation of public funds towards the policies examined should be a principal funding source as this results in superior outcomes. On the other hand, governments should avoid using income tax as a source of finance since this can be highly detrimental to the welfare of urban households.